Aplicativo web para gestão de planos de carreira - Lima, Rafael Alves de (2017)
Career plans are used by companies to achieve promotions and benefits offered by institutions. For institutions it is a way of standardizing the definitions needed for progression in terms of positions, functions, and salary. For the employee, this evaluation serves as a guideline to the work trajectory and as a guide of what is needed to meet the progressions offered by the company and to outline the company institutional career plan. For the public service it is more common to have institutionalized career plans and even in the scope of government (federal, state and municipal). For companies, these plans are usually defined in the scope of each institution. Computational applications can help the management of these plans by the evaluators and the employee who is evaluated. Considering this context, it was developed a web system using Java language and Spring MVC framework, the interface was developed using Angular 5 and Angular Material, and the database used was MySQL.